INTERAKSI LEVERAGE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN MELALUI DIVIDEND POLICY - anik puspa; Ni Luh Anik Puspa Ningsih; Made Pratiwi Dewi (Warmadewa Management and Business Journal (WMBJ), 2021)
Firm value is a reflection of company performance which is explicitly shown through share prices. The stock price is one of the parameters for investors in investing. The higher the stock price, the better the company's performance. This study aims to analyze the interaction of firm value with other financial variables as reflected in the company's financial statements, namely leverage, profitability and dividend policy, which are also considered by investors in long-term investment. The population in this study were Food and Beverages companies on the IDX from 2017 to 2019. The population of this study was 31 Food and Beverages companies, the sampling technique using purposive sampling method was obtained as many as 19 sample companies. Data analysis using path analysis techniques. The findings of this study: (1) Leverage has a positive and significant effect on firm value, (2) Leverage has a negative and significant effect on dividend policy. (3) Profitability has a positive andsignificant effect on firm value, (4) Profitability has a positive and significant effect on dividend policy, (5) Dividend policy has a positive and insignificant effect on firm value. (6) Leverage has a positive and significant effect on firm value through dividend policy mediation. (7) Profitability has a positive and significant effect on firm value through dividend policy mediation.